If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 6) = 105 Reorder the terms: 6(6 + x) = 105 (6 * 6 + x * 6) = 105 (36 + 6x) = 105 Solving 36 + 6x = 105 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 6x = 105 + -36 Combine like terms: 36 + -36 = 0 0 + 6x = 105 + -36 6x = 105 + -36 Combine like terms: 105 + -36 = 69 6x = 69 Divide each side by '6'. x = 11.5 Simplifying x = 11.5
| 3x-3/5=12/5 | | x^2+8x+12=-12 | | 11.2-(18xb)=0.4 | | 4y-1x=8 | | 5+(x+2)=18 | | 2x(-7)= | | 23x+17=178 | | 8.75+3.75=4p | | 8(y+8)=-5-14 | | 19=3y-14 | | 8a+4+(20-55-a)=138.2 | | f(0)=z^2-1+2i | | -6x-3=-57 | | 16a+22(4-a)=70 | | s^2+9=10s | | 9+4+a-17+4=49 | | 7y=4-x | | 4(7x-44)=3-2(x+6) | | 24x-16=3x-2 | | x=-6dlope | | 2n+1+2n+3=52 | | b+5+7b+5=98 | | 5w^2+2=11w | | 2x-3yi+9=-x+2yi+5i | | 156+84= | | 5y+15=45 | | 2(2x+1)-(x+1)=5x-16 | | -70+-35x=-245 | | solvew^2-2w+1=0 | | 3*2=-2(-5)-4 | | 5*2=3(-5)+20 | | 3x-12-5x-10= |